Nuevos hospederos y registros de ácaros fitófagos para Costa Rica: período 2008-2012 - Aguilar, Hugo (2013)
New hosts and records of plant feedingmites for Costa Rica: interval 2008-2012.The phytophagous mite species identified forCosta Rica from 2008 to 2012 are updated.Plant material provided by growers, technicians,students, and interested public, as well as thatcollected by Laboratory of Acarology staff, wasidentified. Sixty-three new host plants groupedin 29 families, for 5 families of phytophagousmites, are mentioned. Tetranychus urticae,family Tetranychidae, was the second species asto number of hosts, being found on 12 new plants.Moreover, other species within the family werefound, i.e. Eutetranychus banksi, Mononychellusplanki, Oligonychus peronis, O. pratensis, O.punicae, O. ununguis, O. yothersi, Paraponychuscorderoi, Tetranychus cinnabarinus, T. ludeni,T. mexicanus, and 3 species in this genuswhich were not identified. Four species in thefamily Tenuipalpidae are recorded: Brevipalpuscalifornicus, B. gliricidiae, B. obovatus, andB. phoenicis. Within the family Tarsonemidae,Phytonemus pallidus is reported, as well asPolyphagotarsonemus latus, with 15 newregisters, the species with the largest numberof hosts on this new period; Steneotarsonemusananas is also reported, associated withpineapple. From the family Eriophyidae, Abacarus doctus, recently described as a newspecies, is reported associated with sugarcane inthe country; likewise Calepitrimerus muesebecki,related to avocado, and 2 species of exposed,un-described eriophyids. Retracrus johnstoni,family Phytoptidae, was collected from Heliconialatispatha, family Heliconiaceae, first record of amite in this genus associated with a family otherthan Arecaceae. Lastly, field diagnosis is alsooffered for some chosen species within the 5families studied.